(untitled) (LEARNing Landscapes, 2021)
In this interview, Carol Rowan recounts how she moved up North to Inukjuak, because she sought to live and learn with Inuit. Following her union with Jobie Weetaluktuk in 1984, and the subsequent births of their three Inuit children, she developed pedagogical approaches informed by and rooted in Inuit ontologies and epistemologies. She discusses how written and spoken Inuktitut language holds culturally specific content. Moreover, she shares how living with land, engaging with Elders, speaking in Inuktitut, and using local materials of the place can serve to displace prevailing Western hegemony with deeper, more intimate understandings of local environments and lifestyles.